1994
DOI: 10.1111/j.1476-5381.1994.tb14831.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible NMDA antagonist properties of drugs that affect high pressure neurological syndrome

Abstract: 1 Previous studies have suggested that a series of drugs modelled on part of the strychnine molecule interfere with the development of high pressure neurological syndrome (HPNS) and it was presumed that this effect was via an action on inhibitory glycinergic transmission. We have now used the rat hippocampal slice preparation to examine the possibility that some of these drugs might instead have an action at the strychnine-insensitive (SI) glycine binding site associated with the NMDA receptor. 2 D-2-Amino-5-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It could be possible that ambient d ‐serine levels in normal conditions are not high enough to induce a sufficient number of activated NMDARs. In the following experiments, we recorded a pair of EPSCs evoked by a pair of electrical stimuli before and during perfusion of d ‐serine (200 μ m ) (Gaiarsa et al 1990; Shuker et al 1994; Li & Han, 2007) in spinal slices of sham‐operated rats. We found that bath perfusion of d ‐serine (200 μ m ) plus NMDA (50 μ m ) did not change either the EPSC amplitude or PPR in neurons ( n = 7) from sham‐operated rats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It could be possible that ambient d ‐serine levels in normal conditions are not high enough to induce a sufficient number of activated NMDARs. In the following experiments, we recorded a pair of EPSCs evoked by a pair of electrical stimuli before and during perfusion of d ‐serine (200 μ m ) (Gaiarsa et al 1990; Shuker et al 1994; Li & Han, 2007) in spinal slices of sham‐operated rats. We found that bath perfusion of d ‐serine (200 μ m ) plus NMDA (50 μ m ) did not change either the EPSC amplitude or PPR in neurons ( n = 7) from sham‐operated rats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A later study provided evidence that mephenesin could be an antagonist of excitatory amino acids [2]. Shuker and coworkers [3] went on to hypothesize that this antagonistic effect on amino acids could be the reason for mephenesin's ability to act as a muscle relaxant. Not surprisingly, on the other hand, mephenesin also has drawbacks including that the muscle-relaxant effect only lasts for a short time, because the drugs are being rapidly metabolized.…”
Section: Introductionmentioning
confidence: 99%